(untitled) (Orfeu, 2020)
Between the 16th and 18th Centuries, the reformed Lutheran world produced texts that have in common the systematical use of the terminology derived from classical rhetoric and poetics to describe musical phenomena. Certainly, the most comprehensive and detailed of these works is the writing by Johann Mattheson, entitled Der vollkommene Capellmeister [“The perfect master-of-chapel”], published in 1739. This article deals with the chapter of Mattheson’s work dedicated to melodic invention, described as the first part of the construction of musical discourse, presents its parts and finally discusses the commonplaces, sources of arguments for invention of musical themes. In presenting Mattheson’s ideas about invention, we intend, in addition to making the content of the text known, to highlight the rhetorical basis of his writings and defend the utility of commonplaces as tools for musical composition in the 17th and 18th Centuries.